1986
DOI: 10.1073/pnas.83.16.6007
|View full text |Cite
|
Sign up to set email alerts
|

The major histocompatibility complex class I heavy chain as a structural subunit of the human cell membrane insulin receptor: implications for the range of biological functions of histocompatibility antigens.

Abstract: The major histocompatibility complex class I heavy chain as a structural subunit of the human cell membrane insulin receptor: Implications for the range of biological functions of histocompatibility antigens ( ABSTRACTMonoclonal antibodies against some of the monomorphic determinants of major histocompatibility complex (MHC) class I molecules reduce insulin binding and precipitate '251-labeled insulin receptor preparations. A monoclonal antibody with specificity for the insulin binding site on the cell membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(58 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…We cannot distinguish between these possibilities, but the accumulated evidence indicates that the cis association and the open MHC I conformers are interdependent events. In this regard, the presence of open MHC I conformers was obligatory for cis association with the insulin receptor to occur, and the cis association was blocked after the exogenous addition of b2m (50,51). The novel cis association that we report in this article may have some implications for the MHC I A splice variant in the fine tuning of classical MHC I A/ TCR and MHC I A/KIR interactions.…”
Section: Discussionmentioning
confidence: 70%
“…We cannot distinguish between these possibilities, but the accumulated evidence indicates that the cis association and the open MHC I conformers are interdependent events. In this regard, the presence of open MHC I conformers was obligatory for cis association with the insulin receptor to occur, and the cis association was blocked after the exogenous addition of b2m (50,51). The novel cis association that we report in this article may have some implications for the MHC I A splice variant in the fine tuning of classical MHC I A/ TCR and MHC I A/KIR interactions.…”
Section: Discussionmentioning
confidence: 70%
“…HLA/IR associate in membranes of lymphocytes, adipocytes, and hepatoma cells (Due et al, 1986;Samson et al, 1986;Cousin et al, 1987;Olsson et al, 1994;Shibata et al, 1995). Our studies have characterized the association and its consequences in B-lymphoblasts, cells that respond to physiological concentrations of insulin (Helderman, 1983;Snow, 1985;Valentine et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Even though many of these associations could be due to genes within the MHC locus, there also is evidence indicating that classical MHC antigens themselves may regulate physiological processes by interacting physically on the cell surface with different ligands. [20][21][22] HFE itself, a nonclassical MHC-I protein, was shown to interact with the transferrin receptor. 23 Recently, a study in ␤ 2 m Ϫ/Ϫ mice demonstrated that MHC-I molecules are functionally required for the development and plasticity of the central nervous system.…”
Section: Resultsmentioning
confidence: 99%